Synovial tissue perivascular edema is associated with altered gait patterns in patients with knee osteoarthritis. Issue 1 (January 2022) - Philpott, H.T.; Carter, M.M.; Birmingham, T.B.; Pinto, R.; Primeau, C.A.; Giffin, J.R.; Lanting, B.A.; Appleton, C.T.
Summary: Objective: To explore mechanisms of mechanoinflammation, we investigated the association between the presence of knee synovial perivascular edema and gait biomechanics that serve as surrogate measures of knee load in patients with knee osteoarthritis (OA). Design: Patients with symptomatic, radiographic knee OA and neutral to varus alignment undergoing total knee arthroplasty or high tibial osteotomy participated in this cross-sectional analysis. All participants underwent 3D gait analysis prior to surgery. Synovial biopsies were obtained during surgery for histopathological assessment. The association between the presence of synovial perivascular edema (predictor) and the external knee moment (outcome) in each orthogonal plane was analyzed using multivariate linear regression and polynomial mixed effects regression models, while adjusting for age, sex, BMI, and gait speed. Results: Ninety-two patients with complete gait and histopathological data were included. When fitted over 100% of stance, regression models indicated substantial differences between patients with and without synovial perivascular edema for knee moments in frontal, sagittal and transverse planes. The knee adduction moment was higher in patients with edema from 16 to 74% of stance, with the largest difference at 33% of stance ( β  = 6.87 Nm [95%CI 3.02, 10.72]); whereas the knee flexion-extension moment differed from 15 to 92% of stance, with the largest difference in extension at 60% of stance ( β  = −10.80 Nm [95%CI -16.20,  −5.40]). Conclusions: In patients with knee OA, the presence of synovial perivascular edema identified by histopathology is associated with aberrant patterns of knee loading throughout stance, supporting the link between biomechanics and synovial inflammation.